Perioperative use of esketamine for the prevention of postpartum depression after cesarean section: a meta-analysis - Yanhong Li; Kuangyu Zhao; Peipei Cao; Qian Wang; Kairui Li; Jun Zhou (BMC Pregnancy and Childbirth)
Summary Background Esketamine has a relatively low adverse effect on mothers and infants during cesarean sections, making it an ideal adjunct in spinal anesthesia. However, its efficacy, dosage, analgesic effects, and safety in preventing postpartum depression (PPD) remain controversial. Methods We searched PubMed, Embase, and Web of Science up to January 18, 2024, for studies examining the perioperative use of esketamine to prevent PPD. Two researchers independently assessed studies for eligibility and risk of bias and extracted data on the incidence of PPD and adverse reactions, EPDS scores, and postoperative pain scores. The study protocol was registered with PROSPERO (CRD42024527906). Findings Of the 214 studies identified, ten (one retrospective study and nine randomized controlled trials) were selected through full-text reading, involving a total of 1975 cases. The PPD incidence within 1 week after childbirth in the esketamine group was significantly lower than that in the control group (RR = 0·49, 95% CI: 0·30 to 0·79, P = 0·004). The score of Edinburgh Postnatal Depression Scale (EPDS) within 1 week postpartum was also significantly lower in the esketamine group (SMD = -1·10, 95% CI: -1·67 to -0·52, P < 0·0005). The pain scores during activity and rest, obtained 48 h postoperatively, showed a significant reduction in the esketamine group. Interpretation Perioperative use of esketamine during cesarean section can prevent the early occurrence of PPD while providing effective analgesia. Our findings may guide the clinical use of esketamine for PPD prevention.